The spiritual-industrial complex: America's religious battle against communism in the early Cold War - Herzog, Jonathan P. (Oxford University Press, 2011)
Preface -- Introduction -- A colossus of straw -- Enemy -- Political institutions -- Security institutions -- Societal institutions -- The renewal, the critics, and the unraveling -- The remains -- Epilogue